Investigation into laser cladding of steel-titanium carbide powder mixtures on a steel substrate - Narva, V. K.; Marants, A. V.; Sentyurina, Zh. A. (Russian journal of non-ferrous metals, 2014)
The influence of the main parameters of laser cladding (the laser radiation power, the scanning speed of the laser beam over the treated surface, the consumption of the cladding material (steel SPN14A7M5-titanium carbide (0–20 vol % TiC)), and titanium carbide content in the powder mixture) on geometric sizes (the height, width, and melting depth of the substrate) of the cladded single layer (bead) has been considered. The structure of the cladded material is investigated using optical and scanning electron microscopes, and the hardness distribution from the substrate to the cladded layer is determined.